Physiological role of anticipatory cardiorespiratory responses to exercise. Issue 5 (5th March 2022) - Miyamoto, Tadayoshi; Sotobayashi, Daisuke; Ito, Go; Kawai, Eriko; Nakahara, Hidehiro; Ueda, Shinya; Toyama, Takeshi; Saku, Keita; Nakanishi, Yasuto; Kinoshita, Hiroshi
Abstract: This study aimed to investigate whether anticipatory cardiorespiratory responses vary depending on the intensity of the subsequent exercise bout, and whether anticipatory cardiorespiratory adjustments contribute importantly to enhancing exercise performance during high‐intensity exercise. Eleven healthy men were provided advance notice of the exercise intensity and a countdown to generate anticipation during 10 min prior to exercise at 0, 50, 80 or 95% maximal work‐rate (Experiment 1). A different group of subjects ( n  = 15) performed a time to exhaustion trial with or without anticipatory countdown (Experiment 2). In Experiment 1, heart rate (HR), oxygen uptake (VO2 ) and minute ventilation (VE ) during pre‐exercise resting period increased over time and depended on the subsequent exercise intensity. Specifically, there was already a 7.4% increase in HR from more than 5 min prior to the start of exercise at 95% maximal work‐rate, followed by progressively augmented increases of 12.5% between 2 and 3 min before exercise, 24.4% between 0 and 1 min before exercise. In Experiment 2, the initial HR for the first 10 s of exercise in the task with anticipation was 11.4% larger compared to without anticipation ( p  < 0.01), and the difference in HR between the two conditions decreased in a time‐dependent manner. In contrast, the initial increases in VO2 and VE were significantly lower in the task with anticipation than that without anticipation. The time to exhaustion during high‐intensity exercise was 14.6% longer under anticipation condition compared to no anticipation (135 ± 26 s vs. 119 ± 26 s, p  = 0.003). In addition, the enhanced exercise performance correlated positively with increased HR response just before and immediately after exercise onset ( p  < 0.01). These results showed that anticipatory cardiorespiratory adjustments (feedforward control) via the higher brain that operate before starting exercise may play an important role in minimizing the time delay of circulatory response and enhancing performance after onset of high‐intensity exercise in man. Abstract : What is the central question of this study? This study aimed to investigate whether anticipatory cardiorespiratory responses vary depending on the intensity of the subsequent exercise bout, and whether anticipatory cardiorespiratory adjustments contribute importantly to enhancing exercise performance during high‐intensity exercise.What is the main finding and its importance? Anticipatory cardiorespiratory control preceding exercise initiation may play an important role in minimizing the delay of circulatory response and physiological efficiency after onset of dynamic exercise, thereby enhancing maximal exercise performance during high‐intensity exercise.